Maternal “Near Miss - Fehmida Shaheen, Attiya Begum (Journal of Rawalpindi Medical College, 2014)
Background : To determine the frequency of maternal near miss, maternal near miss incidence ratio, maternal near miss to mortality ratio and mortality index Methods: In this descriptive study near miss cases were defined based on WHO criteria 2009. Socio-demographic features, causes and ultimate outcome of all the patients were evaluated and all maternal deaths during that period were analyzed and compared Results: There were 15,757 live births and 198 near miss cases during the study period. The maternal near miss incidence ratio was 12.5 per 1000 live births. Maternal near miss to mortality ratio was 4:1 and mortality index was 19.84%. Eclampsia was the leading cause followed by haemorrhage in near miss cases while haemorrhage was found to be the main cause of maternal deaths Conclusion: The review of near miss cases helps delineate continuing threats to maternal health and types of support services most commonly required. The near miss to mortality ratio can be used as a guide to the standard of maternal care. As near miss analysis indicated the quality of healthcare.